In the real world: creating client-centred learning experiences for final year public relations students - Wolf, Katharina (WACE - ACEN Asia Pacific Conference, 2008, 2008)
Higher Education institutions are under pressure to provide the industry with job ready graduates, which require minimum training and fully understand what is required of them in the so-called real world. Institutions who can demonstrate that their learning outcomes reflect the skills and attributes desired by the industry, will in return be equipped with a powerful marketing advantage as their graduates are more likely to be employed (Rundle-Thiele, Bennett, & Dann, 2005).Potential employers are crucial stakeholders in the educational process. Their collaboration in the course design is a promise frequently made to attract students, demonstrating the real-world validity of the program. In addition, this collaboration is often essential to meet accreditation requirements, such as the one set by the Public Relations Institute of Australia, requiring industry reference groups and a minimum period of time spent in the field (Public Relations Institute of Australia, 2008).According to Kerr (2005), public relations employers are particularly looking for graduates with real life and relevant work experience. In order to enrich student learning and understanding of professional public relations practice, the final year Public Relations Consultancy unit has been designed around a ?real life client?, which is selected on a semester basis. This paper provides an insight into the unit design, the mix of individual and group assignments, client motivation and students? learning experiences, including an opportunity for top performers to present ? or ?pitch? - their ideas and recommendations in an authentic boardroom-like situation.